Trends on Maternal Mortality in the Republic of Benin and Comparison with the Neighboring Countries - Konnon, Romeo; Semyatov, Said; Soyunov, Muhammednazar; Sokhova, Zalina; Zulumyan, Tatevik (Medicine, Law & Society, 2020)
The maternal mortality ratio in the Republic of Benin in 2015 was still high – 405 per 100,000 live births. The delay in consultation and timely treatment, unavailability of medical facilities and lack of skilled care are the principal factors contributing to maternal deaths in Benin. Consequently, the rate of such preventable causes of maternal deaths like obstetric haemorrhage (38.40 percent and pre-eclampsia/eclampsia (14.30 percent) remains high in the country, and even HIV continued being one of the indirect causes of maternal deaths in 2017 – one percent. High rate of complications associated with pregnancy and birth in adolescent girls is another cause of maternal deaths in the Republic of Benin. Despite the efforts of the Government aimed at improving health care, it is unlikely that we will achieve the United Nations Sustainable Development Goals 3.1. – the reduction of maternal mortality ratio to less than 70 per 100,000 live births by 2030.